2011
DOI: 10.1182/blood-2010-08-303123
|View full text |Cite
|
Sign up to set email alerts
|

A role for Blimp1 in the transcriptional network controlling natural killer cell maturation

Abstract: IntroductionNatural killer (NK) cells are innate lymphocytes specialized in cytokine production and cytotoxicity toward tumors and virusinfected cells. NK cells develop in the bone marrow from hematopoietic stem cells (HSCs) via lymphoid precursors. 1 The earliest committed NK-cell precursors can be isolated from lineage marker-negative fetal thymus or adult bone marrow and express high levels of the interleukin 15 (IL-15)/interleukin 2 receptor␤ (IL-2R␤) chain (CD122 2 ). NK-cell precursors then undergo matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
126
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 50 publications
14
126
0
Order By: Relevance
“…7B and C). Among these genes, Prdm1 (Blimp1), Kit, and Tnfrsf9 are of special interest, since their expression is induced by IL-15 and they are known to be involved in NKC proliferation (57)(58)(59). Expression of Prdm1 was upregulated in Runx3 (Fig.…”
Section: Il-15 Alone (41) Administration Of Il-15/r␣ To Wt or Runx3mentioning
confidence: 99%
“…7B and C). Among these genes, Prdm1 (Blimp1), Kit, and Tnfrsf9 are of special interest, since their expression is induced by IL-15 and they are known to be involved in NKC proliferation (57)(58)(59). Expression of Prdm1 was upregulated in Runx3 (Fig.…”
Section: Il-15 Alone (41) Administration Of Il-15/r␣ To Wt or Runx3mentioning
confidence: 99%
“…Prdm1-induced maturation of lymphocytes is correlated with the ability of Prdm1 to repress numbers of genes critical for mature B cell identity and cellular proliferation [5,[8][9][10][11][12][13]. Prdm1 is also needed for the activation of T cells [14][15][16][17][18], the differentiation of myeloid lineage [19] and the maturation of nature killer (NK) cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…These loss-of-function studies (4,5) indicate that Blimp-1 is required for terminal differentiation by the activated CD8 + T cell, which it for two other lymphocytic lineages, the B (8) and NK (9) cells. T-bet promotes Blimp-1 expression in the natural killer (NK) cell (9), and a similar role may be expected in the CD8 + cell, because T-bet-(2) and Blimp-1-deficient (4, 5) CD8 + T cells have similar differentiation phenotypes. Moreover, in vitro studies have shown that T-bet expression enables signaling by the IL-2 receptor to induce Blimp-1 transcription (10).…”
mentioning
confidence: 99%